The Relationship Between My Fairy Following Social Media Influencers and the Buying Decision of this Local Brandsex (Correlation Research on Generation Z) - Nadhifa Yasmin Tamariyani; Intan R. Mutiaz (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
This study aims to determine the relationship between consumptive behavior and strategies for using social media influencers with the decision to buy local unisex brands among generation Z. The questionnaire was used as an instrument in data collection which was distributed via google form to 276 respondents who came from generation Z or someone aged 12 to 27 years who live in the city of Jabodetabek (Jakarta, Bogor, Depok, Tangerang, Bekasi). Instrument testing uses validity and reliability tests with 22 sub-indicator items, it is known that all items are valid and reliable. The results of the normality test show that the data is normally distributed with a significance value of 0.062. The linearity test obtained the results of 0.146 > 0.05, it can be said that the variables in this study were linear. The results showed that: 1) There is a positive relationship between the strategy of using social media influencers and the decision to purchase local unisex brand fashion products by Generation Z. 2) There is a positive relationship between Generation Z consumptive behavior and the decision to buy local unisex brand fashion products. 3) There is a positive relationship between the strategy of using social media influencers and consumptive behavior together with the decision to purchase unisex local brand fashion products. The contribution of consumptive behavior and influencer-following behavior to purchasing decisions is 39.1%, and the rest is influenced by other variables not tested in this study.